1994
DOI: 10.1159/000098631
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Study of Spinal Cord Stimulation versus Reoperation for Failed Back Surgery Syndrome: Initial Results

Abstract: Spinal cord stimulation (SCS) has been reported to be effective treatment for the failed back surgery syndrome in a number of retrospective case series. Its retrospectively reported results compare favorably with those of neurosurgical treatment alternatives, such as reoperation and ablative procedures. There has been no direct prospective comparison, however, between SCS and other techniques for pain management. We have undertaken a prospective, randomized comparison of SCS and reoperation in patients with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
6

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(57 citation statements)
references
References 0 publications
2
49
0
6
Order By: Relevance
“…44 Despite the extensive literature on SCS for FBSS, only one randomized study has yet been performed. 45 In this study SCS was compared to re-operation in patients with persistent radicular pain (with and without low back pain) following lumbosacral spine surgery. The primary outcome measure was the frequency of cross over to the alternative procedure, if results of the ®rst intervention were unsatisfactory after 6 months.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…44 Despite the extensive literature on SCS for FBSS, only one randomized study has yet been performed. 45 In this study SCS was compared to re-operation in patients with persistent radicular pain (with and without low back pain) following lumbosacral spine surgery. The primary outcome measure was the frequency of cross over to the alternative procedure, if results of the ®rst intervention were unsatisfactory after 6 months.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…[18] Taylor ve ark. yaptığı 72 hastayı içeren çalışmada, spinal kord stimülasyonu yapılan hastalarla (%37.5) tekrar operasyon geçiren hastalar (%11.5) karşılaştırıldı-ğında ağrıda %50'den fazla azalma tespit edilmiş.…”
Section: Discussionunclassified
“…They concluded that approximately 50 to 60% of FBSS experienced a clinically significant pain relief of more than 50% during SCS treatment at long-term (mean, 16 months; range, 1-45 months) follow-up visits. Furthermore, North et al presented some evidence in favor of SCS in relieving neuropathic pain compared to reoperation for FBSS, although results did not reach significance (North et al, 1994). SCS provides significant increased pain alleviation compared to conventional treatment when administrated in carefully selected FBSS patients suffering neuropathic pain.…”
Section: Scs For Failed Back Surgery Syndromementioning
confidence: 99%